Al-Qur’an sebagai Kitab Suci - Lukman, Fadhli (Lajnah Pentashihan Mushaf Al-Qur'an, 2014)
As the center of Islamic civilization, the Qur’an receives numerous intellectual responses both from Muslim and Western scholars within history. One of the prominent names of Western scholars who deals very much with the Qur’an is Jane Dammen McAuliffe. This article discusses the ontological view of the Qur’an of Jane Dammen McAuliffe, within a context of a new growing interest of western scholarship to see the Qur’an. Applying phenomenological and analytical methods of analysis, the articles ends in conclusions: [1] Muslims’ views on the Qur’an tend to be theologically oriented, while the Westerns have resulted some polemical conclusions [2] however a new growing interest in the West, in which Jane Dammen McAuliffe belongs to, sees the Qur’an as a scripture, that emphasizes the importance of relation between the text and human’s belief in the text; the Qur’an and Muslims. Keyword: the Qur’an, Jane Dammen McAuliffe, definition, scripture, relation.